Developing electronic participation framework for public policy formulation in Malaysia - Salamat, Mohamad Aizi (2015)
Electronic participation (e-participation) is a research domain that focuses on the development of information and communication technology (ICT) to support participation in a nation‟s governance processes. One of the problems in implementing this process in Malaysia is the lack of participation from its citizens in providing inputs to be used in the nation‟s public policy formulation processes. In addition, there is a lack of research on e-participation and framework that supports the public policy formulation. Therefore, in this study, the researcher attempts to look at how the public can involve and play their part in the process of drafting the nation‟s public policies by utilizing the information technology mechanism. The main objective of this study is to develop a framework for the implementation of eparticipation in the public policy formulation processes. To achieve this objective, the public‟s levels of perception and satisfaction with the current Government‟s eparticipation initiatives in the public policy formulation and implementation process are identified. Questionnaires, interviews, observations, and analysis of relevant documents were the methods used in this study. Actor Network Theory (ANT) from the socio-technological perspective was applied in this study in order to analyze the development of the e-participation framework. The proposed e-participation framework was then assessed using the Delphi Method to seek the consensus from the experts appointed. As a result, the e-participation framework for public participation in Malaysia was successfully developed. This e-participation framework enables people to jointly contribute towards the formulation of public policy. From the theoretical perspective, the framework implies that ANT provides a strong foundation for policy making process of aligning the heterogeneous nature of public participation. In practice, the ICT tools for public participation will hopefully enable a wider participation in contributing to a democratic practice. Keywords: Citizen participation, Electronic participation, Public policy, Actor Network Theory (ANT), Delphi Method